PELAKSANAAN DAK FISIK BIDANG PENDIDIKAN DI KABUPATEN AGAM - Lisna Sulinar Sari (Program Studi PPKn FIS UNJ & Asosiasi Profesi PPKn Indonesia, 2019)
The aim of this study was to find out the implementation of the Physical Special Allocation Fund (DAK) in the Basic Education level in Agam Regency. This study uses a qualitative approach. Respondents were Head of Elementary and junior SecondarySchool Division, as well as managers of Physical DAK in Elementary and Middle School. Data collection were carried out using clustered group discussions (DKT) and secondary data. Analysis data used qualitative descriptive technique. The results of the study show that the implementation of education infrastructure improvement is carried out in a self-managed manner and the procurement of educational facilities is carried out by auction or by e-catalog. All of the education infrastructure improvements can be carried out (100%) both in elementary and junior high schools. Whereas not all can be implemented to improve education facilities, especially in elementary schools. To procure library collections in the Elementary School, Elementary School Division in the regency must refund as much as IDR 2.6 billion, because it cannot carry out the procurement of library collections due to the absence of providers who pass the selection for auction. Procurement of educational equipment and media can be implemented in Junior Secondary School, because all goods needed in the procurement of equipment and educational media are in the e-catalog, making it easier for DAK managers to procure an increase in educational facilities. In addition, the ecatalog procurement process is faster and safer.